The language of the English street sign - Cook, Vivian 1940-2021 (Multilingual Matters, 2022)
This book opens readers' eyes to something they see all the time but take for granted: street signs. It is a portrait of the signs on modern English streets: what they look like, who and what they are for, how they link to English history and how they form part of life in multilingual England today